2016
DOI: 10.1016/j.cbpa.2016.06.019
|View full text |Cite
|
Sign up to set email alerts
|

Histone deacetylase 3 (HDAC 3) as emerging drug target in NF-κB-mediated inflammation

Abstract: Activation of inflammatory gene expression is regulated, among other factors, by post-translational modifications of histone proteins. The most investigated type of histone modifications is lysine acetylations. Histone deacetylases (HDACs) remove acetylations from lysines, thereby influencing (inflammatory) gene expression. Intriguingly, apart from histones, HDACs also target non-histone proteins. The nuclear factor κB (NF-κB) pathway is an important regulator in the expression of numerous inflammatory genes, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
111
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 120 publications
(112 citation statements)
references
References 83 publications
0
111
0
1
Order By: Relevance
“…This could aid in obtaining selective anti-inflammatory effects via regulation of NF-κB acetylation on specific lysines. Based on the important role of HDAC3 in deacetylation of specific NF-κB p65 lysines18, HDAC3-selective inhibitors may be interesting candidates for studies in mice. In support of this, the HDAC3-selective inhibitor RGFP966 was previously shown by us to increase IL10 expression and reduce pro-inflammatory gene expression in PCLS.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This could aid in obtaining selective anti-inflammatory effects via regulation of NF-κB acetylation on specific lysines. Based on the important role of HDAC3 in deacetylation of specific NF-κB p65 lysines18, HDAC3-selective inhibitors may be interesting candidates for studies in mice. In support of this, the HDAC3-selective inhibitor RGFP966 was previously shown by us to increase IL10 expression and reduce pro-inflammatory gene expression in PCLS.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast it has been demonstrated that HDAC1 negatively regulated NF-κB-mediated gene transcription through association with p65, whereas HDAC2 does not interact with NF-κB directly but regulates NF-κB activity via its interaction with HDAC117. HDAC3 has been reported to deacetylate specific lysines of NF-κB p6518. It was shown that HDAC3 is required for IL-1-induced gene expression, where the positive regulatory role of HDAC3 involves binding to the NF-κB p65 subunit and deacetylation of various inhibitory lysine acetylations19.…”
mentioning
confidence: 96%
“…Some of these modifications such as DNA methylation and histone acetylation lead to conformational alterations of chromatin structure and, in turn, gene accessibility, which can thus influence transcriptional activities . Whereas acetylation of lysine amino acid in histone promotes transcriptional activation and cell apoptosis through the effects on compact chromatin structure, a high level of histone deacetylation by histone deacetylase (HDAC) overexpression induces translational repression and thereby a number of pathological conditions such as cancer and inflammation . Intriguingly, HDAC family enzymes are emerging as an attractive therapeutic target of numerous human diseases that are linked to aberrant epigenetic states.…”
Section: Histone Deacetylasementioning
confidence: 99%
“…Moreover, it has been proposed that combination of the HDAC inhibitors with traditional chemotherapeutic medication can further improve clinical outcomes, which will hopefully go beyond hematologic indications to treat solid tumors . Also, because many inflammatory signaling pathways such as nuclear factor‐κB and STAT3 are also regulated by posttranslational modification of histone proteins, HDAC inhibitors have been accordingly recognized to play a role in affecting autoimmune‐mediated pathological conditions . Indeed, an HDAC inhibitor was revealed to minimize pain and neutrophilia and to improve physical function in patients with juvenile idiopathic arthritis, owing to downregulation of inflammatory cytokine IL‐1β and TNF‐α.…”
Section: Histone Deacetylasementioning
confidence: 99%
“…However, multiple other cytosolic and nuclear proteins are also regulated by reversible acetylation. Two of the most notable acetylated proteins whose functions are of prime importance in the survival of many tumor cell types are heat shock protein 90 (HSP90) and the p65 subunit of NFκB (Leus, Zwinderman, & Dekker, 2016; Rodrigues, Thota, & Fraga, 2016). …”
Section: Text Elementsmentioning
confidence: 99%